(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The coordination polymer [NaFe(EDTA)(H2O)]n ·H2O was comprehensively characterized through elemental and structural analyses, including energy-dispersive X-ray spectroscopy (EDX), molecular electrostatic potential (MEP) surface mapping, and crystal packing investigation. The EDX spectrum revealed prominent Fe Kα and Fe Kβ signals together with the characteristic Na Kα peak, confirming the presence of iron and sodium in the synthesized material and supporting the proposed chemical composition. Molecular electrostatic potential analysis provided valuable information on the charge distribution within the complex, identifying electron-rich regions localized around the carboxylate oxygen atoms of the EDTA ligand and electron-deficient regions associated with coordinated and lattice water molecules. These features indicate favorable sites for intermolecular hydrogen-bonding interactions and contribute to the stabilization of the crystal structure. Crystal packing analysis demonstrated the formation of an extended one-dimensional coordination polymer in which Fe(III) centers are interconnected through EDTA ligands and further stabilized by sodium ions and a network of O-H···O hydrogen bonds involving coordinated and crystallization water molecules. The synergistic combination of coordination bonds, electrostatic interactions, and hydrogen bonding results in a robust supramolecular architecture. The obtained findings provide a deeper understanding of the structural organization, intermolecular interactions, and physicochemical characteristics of this iron-EDTA-based coordination polymer, highlighting the importance of multidentate ligands in the design and construction of extended metal-organic frameworks and related functional materials.